ANALISA AYAT DAN HADIST TENTANG KEWARISAN LAKI-LAKI DAN PEREMPUAN SERTA PROBLEMATIKANYA - Harahap, Zulfan (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2023)
There are fifteen male heirs consisting of sons, grandsons, fathers, father's grandfathers, full brothers, father's brothers, mother's brothers, sons. brother's son, father's brother's son, father's uncle, father's uncle, son's son, father's uncle's son, husband, and master of a liberated man slave. There are ten female heirs. They were all daughters, granddaughters of sons, mothers, maternal grandmothers, paternal grandmothers, full sisters, father's sisters, mothers' sisters, wives, and female masters who freed slaves.